A review of proximal inputs to the near response. (January 2016) - Fogt, Nick; Toole, Andrew J; Rogers, David L
Abstract : Maddox proposed that the perceived nearness of a target could influence the ocular vergence response. Proximal inputs have been used to refer to all static and dynamic cues to depth other than disparity and blur. In this paper, we review a number of studies in which proximal influences have been assessed. While general agreement exists that proximal contributions are significant when blur and disparity cues are absent (open‐loop conditions), there are conflicting reports on the role of proximal vergence and accommodation under closed‐loop conditions.